If the following equation has infinite number of roots, what is the sum of the constants :
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Make the base equal to 3 on both sides, you will get
3^((a-10)x+33)=3^(3x+3b)
then divide by 3^(3x+3b) on both sides gives 3^((a-13)x+(33-3b))=1
So to equate both side we must have a=13; 33-3b=0 or b =11
Thus a+b=24.